The rise of mammals - Attenborough, Richard, 1926-; British Broadcasting Corporation (Wilmette : Films Inc., 1981)
Naturalist Richard Attenborough offers a detailed study of the many marsupial species, paying special attention to the primitive marsupials found in Australia
Keywords: Marsupalia -- Australia; Mammals -- Australia